An interesting case of acute pancreatits - Kalidindi, Lakshmipriya; Linkeshavan, Mohana; Kalappan, Mahendra Kumar; Mohanan, Jagadeesan; Rajendran, Kannan (International Journal of Advances in Medicine, 2022)
Hypertriglyceridemia (HTG) is the third most common cause of acute pancreatitis but it is relatively rare and requires a high level of clinic suspicion. We report a 30 years old male with no co-morbidities who is a non-alcoholic, non-smoker presented with epigastric pain associated with vomiting for two days. His vitals were stable and systemic examination was unremarkable. Serum lipase levels were elevated [7365 U/l (<40 U/l)]. Computed Tomography of the abdomen suggested acute pancreatitis with extensive peri-pancreatic inflammatory changes with no evidence of pancreatic necrosis. Serum triglycerides were found to be elevated (3450 mg/dl). A diagnosis of HTG induced acute pancreatitis was made. During evaluation he was found to be diabetic. He was treated with intravenous fluids, IV insulin infusion, and other supportive measures. He was started on statins, fenofibrate and omega 3 fatty acids. His condition improved and triglyceride levels after two days were in a declining trend and he was discharged on the same. He was currently under follow up and his serum amylase, serum lipase, serum triglycerides were normal. This case report provides insight into rare cause of acute pancreatitis-HTG which if diagnosed at the earliest can be treated promptly.